Managing Infants Exposed to Maternal Chorioamnionitis by the Use of Early-Onset Sepsis Calculator. (April 2019) - Sharma, Vinay; Adkisson, Constance; Gupta, Kunal
Objective . To reduce neonatal intensive care unit admission rate (NAR) and antibiotic utilization rate (AUR) in ≥36 weeks gestational age infants exposed to maternal chorioamnionitis (MC) through the application of early-onset sepsis calculator (EOSCAL). Study Design . This is a single-center cohort study. All infants born ≥36 weeks gestational age and exposed to MC were compared for NAR, AUR, and laboratory evaluation rate (LER) 2 years after and 1 year before the implementation of EOSCAL. Results . There is a significant decrease in NAR ( P < .001), AUR ( P < .04), and LER for blood culture, complete blood count, and C-reactive protein ( P < .001) after implementation of EOSCAL. If infants received antibiotics, it was for significantly less number of doses ( P < .01). There was no increase in the readmission rate. Conclusion . Use of EOSCAL significantly decreases the rate of NAR, AUR, and LER in infants exposed to MC, without affecting readmission rates and late antibiotic use.